2019
DOI: 10.1111/imj.14634
|View full text |Cite
|
Sign up to set email alerts
|

Are external management consultancies effective in healthcare improvement, do they reflect value for money and what are the alternative models?

Abstract: Despite the increasing use and costs associated with external management consultancy for healthcare improvement, there is a paucity of formal evaluations examining impact. This paper aims to: (i) discuss the potential benefits and disadvantages of external consultancies in addressing complex healthcare challenges and delivering healthcare improvement in Australia; and (ii) explore potential alternative models, including internal consultancy and hybrid models delivered through platforms of collaborative experti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…While our research has been focused on New Zealand, there are studies which highlight similar trends in the United Kingdom as well as in Australia. 6,10,11 The reliance on ECCs appears to be a sectorwide problem, and therefore demands a comprehensive How many contractors, consultants, including those providing professional services, were engaged or employed in 2016/2017 and what was the estimated total cost? How did this compare to each of the previous four financial years, both in terms of the number engaged and the total cost?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While our research has been focused on New Zealand, there are studies which highlight similar trends in the United Kingdom as well as in Australia. 6,10,11 The reliance on ECCs appears to be a sectorwide problem, and therefore demands a comprehensive How many contractors, consultants, including those providing professional services, were engaged or employed in 2016/2017 and what was the estimated total cost? How did this compare to each of the previous four financial years, both in terms of the number engaged and the total cost?…”
Section: Discussionmentioning
confidence: 99%
“…While our research has been focused on New Zealand, there are studies which highlight similar trends in the United Kingdom as well as in Australia. 6 , 10 , 11 The reliance on ECCs appears to be a sector-wide problem, and therefore demands a comprehensive approach when being investigated. Our research is a start; further research is needed, including across other areas of the public sector which are also known to rely on ECCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this sentiment as well as fuelling it, governments have for several years now kept level or even reduced funding for academic research ( Atkinson and Foote, 2019 ). Alongside this, management consultants are increasingly tasked with the development of healthcare solutions in the UK ( Kirkpatrick et al , 2019 ) as well as in Australia ( Skouteris et al , 2019 ), even though the increased expenditure on such consultants has been found to be associated with organisational inefficiency ( Kirkpatrick et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%